Effects of diet during pregnancy on placental efficiency in Holstein × Gyr Heifers - Oliveira, Kellen Ribeiro (Universidade Federal de Viçosa, 2022)
Placenta and fetal growth depend of umbilical and uterine blood flow, and adverse conditions may impact the animal's entire life. This study aimed to evaluate the effects of diet during pregnancy on the blood supply to the placenta in two nutritional regimes throughout the gestational period, colostrum production, the newborn parameters and uterine involution. A total of fourteen Holstein × Gyr heifers with an average body weight of 446 kg ± 46.7 kg and age of 25 ± 3.9 mo were randomly assigned to the following treatments: moderate body weight gain (MOG, n = 7), the usual at tropical systems, where heifers were fed to achieve 0.5 kg/d of average daily gain (ADG); and high body weight gain (HIG, n = 7), where heifers to achieve 0.75 of ADG. The heifers received the same diet with corn silage and a concentrate-based diet twice daily varying the dry matter (DM) according to ADG, adjusted each 28 d of each treatment until calving. The placentome vascularization was assessed by using a Color-Doppler ultrasound. After calving, cotyledon was sampled to analyze mRNA expression of genes involved in angiogenesis process in the placenta. After birth, calves were weighed, received colostrum, and had their efficiency of transfer of passive immunity (TPI) assessed. The MOG heifers had a greater number of cotyledons (81.5 ± 12.9 vs. 63.6 ± 10.5), and continuous growing in placentome vascularization compared to HIG heifers. Indeed, MOG heifers had a greater the mRNA expression of VEGFB and IGFR1, as well as estradiol concentration before calving compared to HIG heifers. On the other hand, a greater colostrum production was observed in HIG heifers (3.94 ± 1.05 vs. 2.18 ± 1.57), but with lower quality (25.2 ± 0.51 vs. 29.5 ± 0.65; Brix %). Further, postpartum serum calcium and glucose were greater on d 8 in MOG heifers, but an equal immune response and uterus involution. The calf from HIG heifers had a better vitality score and equal body weight (BW) at birth and efficiency in TPI. Collectively, our results show that moderate nutritional regimen during gestation of dairy heifers undergo maternal adaptations in the placenta to support gestation without damage to fetus and their postpartum life. Keywords: Cotyledon. Doppler ultrasound. Fetal programming. Gene expression

O crescimento placentário e fetal é dependente do fluxo sanguíneo umbilical e uterino, condições adversas podem impactar em toda a vida do animal. Este estudo tem como objetivo avaliar os efeitos da dieta materna no suprimento sanguíneo placentário em dois regimes nutricionais durante a gestação, produção de colostro, parâmetros do recém-nascido e involução uterina. Quatorze novilhas Holandês × Gir com peso inicial de 446 ± 46,7 kg foram aleatoriamente destinadas a um dos seguintes tratamentos: ganho de peso moderado (MOG; n = 7), onde eram alimentadas para atingir 0,5 kg/dia e alto ganho de peso (HIG; n = 7), onde eram alimentadas para o ganho de 0,75 kg/dia. As novilhas recebiam duas vezes ao dia a mesma dieta composta por silagem de milho e concentrado variando a quantidade de MS fornecida de acordo com o GMD, ajustado a cada 28 dias de cada tratamento até o parto. A vascularização do placentoma foi avaliada utilizando um ultrassom com Color Doppler. Pós-parto, os cotilédones foram contados e amostrado para analisar a expressão de mRNA de genes relacionados com o processo de angiogênese na placenta. Após o nascimento, os bezerros foram pesados, receberam colostro e foi avaliada a eficiência na transferência de imunidade passiva (TIP). As novilhas de MOG tiveram maior número de cotilédones (81.5 ± 12.9 vs. 63.6 ± 10.5), e crescimento contínuo da vascularização de placentoma. Ainda, as novilhas de MOG tiveram maior expressão de mRNA de VEGFB (P = 0,0397) e IGFR1 (P = 0,0470), assim como a concentração pré-parto de estradiol comparado com novilhas de HIG. Por outro lado, foi observada uma maior produção de colostro nas novilhas com HIG (3.94 ± 1.05 vs. 2.18 ± 1.57), porém com menor qualidade (25.2 ± 0.51 vs. 29.5 ± 0.65; Brix %). Ainda, cálcio e glicose séricos foram maiores no dia 8 para novilhas de MOG. Bezerros originados de novilhas HIG tiveram melhor escore de vitalidade, mas peso ao nascer e eficiência na transferência de imunidade passiva similar. Em conclusão, os resultados demonstram que um regime nutricional moderado durante a gestação de novilhas leiteiras promove adaptações na placenta para suportar a gestação sem danos ao feto e sua vida pós-parto. Palavras-chave: Cotilédone. Expressão gênica. Programação fetal. Ultrassom Doppler.
Efeitos da dieta materna durante a gestação na eficiência placentária em novilhas Holandês × Gir
Keywords: Novilhos - Nutrição; Novilhos - Gestação; Cotilédone; Doppler, Ultrassonografia; Desenvolvimento fetal; Expressão gênica; Nutrição e Alimentação Animal